ATTEMPTED SYNTHESIS OF BIS-SPIROEPOXIDE DITHIANEDIOXIDE - Ritmaleni Ritmaleni; Varinder K. Aggarwal (Indonesian Journal of Pharmacy, 2012)
The  bis-spiroepoxide  dithiane  dioxide  has  been attempted  to  be  synthesised  as  its  role  as  an  intermediate  in the  synthesis  of  diaminopimelic  acid  (DAP).  The  first  method was  carried  out  by  reacting  the  3-dithiane-2-diethylphosphonate  4  with  an  aqueous  solution  of  the commercially  available  glutaraldehide  resulting  the  bis-ketene dithiane  dioxide  5.  The  second  alternative  method  was involving  the  ozonolysis  of  cyclopentene   7  in  the  synthesis  of bis-ketene dithiane dioxide  5 in  four step reactions  which gave moderate to good yield. Unfortunately, epoxidation process  for the bis-ketene dithiane dioxide 5 was still unsuccess yet.Key  words:  synthesis,  diaminopimelic  acid,  bis-spiroepoxide  dithiane dioxide